Challenges in Globalisation of Global Software Development: A Conceptual Study of Co-locating Key Roles and its Impact on Product Life Cycle - Saketharaman, Umasankar; Anandkumar, Victor (Ushus Journal of Business Management, 2018)
This study characterises the results of published scientific research in the field of Global Software Product Development (GSD). Based on the analysis of about 22 scholarly articles published between 2001 and 2014, it is observed that in spite of issues and challenges faced in its implementation, GSD is a business necessity. To ensure more successful realisation of the benefits of GSD, co-locating some of the key-roles at global locations along with software development could be exercised. This could have a positive impact on the software product life cycle. This relationship needs to be validated by further research backed with empirical data.